“Comportamiento agronómico del cultivo de soya (Glycine max L.), a la aplicación de tres extractos de algas marinas, en la zona de Puebloviejo”. - Moreira Sisalema, José Manuel (2018)
VII. SUMMARY The present experimental work was carried out in the lands of Mr. Medardo Bustamante Miranda, located at Km 5.0 of the Zapote-Pechiche road, of the Puebloviejo canton, province of Los Ríos, with geographic coordinates of 277438.26 UTM of west longitude and 110597.97 UTM of south latitude. This area has a humid tropical climate, with an annual average temperature of 24 0C and a height of 8 m.s.n.m. The objectives were: to determine the agronomic behavior of the soybean crop to the application of seaweed extracts; identify the most influential product and dose on the yield of the soybean crop; evaluate the phytotoxicity to the crop by the application of seaweed extracts and economically analyze the treatments according to the yields. The soy variety P-34 was used as seed material. The present experimental work had 7 treatments and 3 repetitions, consisting of FertiEstim in doses of 1.5 and 2.0 L / ha, Kelpak 1.5 and 2.0 L / ha; Basfoliar Algae 1.5 and 2.0 L / ha and a Control without application of seaweed extract. The experimental design of Complete Blocks at Random was used, with 7 treatments and three repetitions. To perform the evaluation of the means of the treatments, the analysis of variance was used and the comparison of means was made with the Tukey test at 95% probability. For the execution of the trial, all the practices and agricultural tasks that the crop requires for its normal development were carried out, such as land preparation, sowing, weed control, phytosanitary control, fertilization, irrigation and harvesting. To estimate the effects of the treatments, the data on plant height, days to flowering and maturation, number of pods and seeds per plant, number of seeds per pod, weight of 100 seeds, yield per hectare and economic analysis were evaluated. Based on the results obtained, it was determined that the highest plant height was obtained with the use of Basfoliar Algae in a dose of 2.0 L / ha; the treatment that was used FertiEstim, in doses of 1.5 L / ha influenced so that the crop flourishes and matures in less time; with the treatment that Basfoliar Algae was used in a dose of 2.0 L / ha, a greater number of pods and seeds were reported per plant and number of seeds per pods; the weight of 100 seeds obtained higher average with the use of FertiEstim (Ascophyllum nodosum), in doses of 1.5 L / ha and the highest yield of grain, as well as net benefit was registered with the treatment of Basfoliar Algae in doses of 2.0 L / ha, with $ 1257,04.